My Name is Your Name: Anthroponyms as Divine Attributes in the Greco-Roman World - Gasparini, Valentino; Alvar Ezquerra, Jaime; Bonnet, Corinne (De Gruyter, 2025)
Divine epithets serve a variety of purposes, with the most frequent being those related to the locations and functions of the gods. Epithets derived from individual names, however, have received less attention. While few studies have focused on the Greek world, research on the Latin-speaking Mediterranean is still sporadic. Such "anthropophoric" onomastic attributes have often been interpreted as related to the name of a cult founder. Yet, such a practice rather suggests various forms of relationships between the god and the individual (or group) whose name shapes the epithet. These dynamics of "individualisation" of a deity require further exploration. This collective book provides, for the first time, a detailed catalog of 398 Greek and Latin occurrences from the broad circum-Mediterranean area (including Greece, Anatolia, the Levant, North Africa, the Iberian peninsula, Central Europe, Italy, and Rome), related to 45 divinities and 191 different epithets. Multiple case studies ranging from the 5th or 4th century BCE to the 4th century CE, examined through different chronological, geographical, and thematic perspectives, offer valuable insights into local and regional strategies of religious appropriation